2022
DOI: 10.1186/s13690-021-00755-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sedentary behavior patterns during the transition from childhood to adolescence and their association with adiposity: a prospective study based on compositional data analysis

Abstract: Background To date, no longitudinal study using a compositional approach has examined sedentary behavior (SB) patterns in relation to adiposity in the pediatric population. Therefore, our aims were to (1) investigate the changes in SB patterns and adiposity from childhood to adolescence, (2) analyze the prospective compositional associations between changes in SB patterns and adiposity, and (3) estimate the changes in adiposity associated with substituting SB with physical activity (PA) of diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 51 publications
(45 reference statements)
2
15
0
Order By: Relevance
“…This might lead to a loss of information that may be a hallmark of childhood obesity, making it unclear which specific intensities are most strongly related to adiposity. Some light has been shed on this question by compositional analyses of waking hours sedentary time, LPA, MPA, and VPA among Czech [ 57 , 58 ] and American youth [ 59 ], which observed VPA to be negatively and significantly associated with adiposity indicators relative to the other behaviours. These results support ours and demonstrate how the commonly reported finding that MVPA has the strongest influence on adiposity-related indicators relative to other physical behaviours actually masks the potentially more important contribution of higher intensity activities, while simultaneously amplifying the influence of lower intensity activities that fall within the MVPA range, as determined by the chosen absolute intensity cut-points.…”
Section: Discussionmentioning
confidence: 99%
“…This might lead to a loss of information that may be a hallmark of childhood obesity, making it unclear which specific intensities are most strongly related to adiposity. Some light has been shed on this question by compositional analyses of waking hours sedentary time, LPA, MPA, and VPA among Czech [ 57 , 58 ] and American youth [ 59 ], which observed VPA to be negatively and significantly associated with adiposity indicators relative to the other behaviours. These results support ours and demonstrate how the commonly reported finding that MVPA has the strongest influence on adiposity-related indicators relative to other physical behaviours actually masks the potentially more important contribution of higher intensity activities, while simultaneously amplifying the influence of lower intensity activities that fall within the MVPA range, as determined by the chosen absolute intensity cut-points.…”
Section: Discussionmentioning
confidence: 99%
“…For partition models, linear regression models were used to examine the association between baseline movement behaviors (all five independent variables together in the model [sedentary time, LPA, MPA, VPA, and sleep]) and follow-up adiposity (dependent variables). For isotemporal substitution models, movement behaviors were summed to create a total time variable (sum of sedentary time, LPA, MPA, VPA, and sleep), and individual movement behaviors were also divided by 10 to create 10-min increments like other studies with low amounts of VPA relative to MPA and LPA (15,17,32). To evaluate the association of substituting 10 min of sedentary time, all other movement behaviors (LPA, MPA, VPA, and sleep represented as 10-min increments) were included as independent variables, total time was included as a covariate, and follow-up adiposity was the dependent variable.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, substituting sedentary time with MVPA was associated with lower visceral adipose tissue (VAT) in 412 children (ages 7–12 yr) (16). A longitudinal study of 88 children (ages 9.2 ± 0.9 yr) found that allocating sedentary time to VPA was associated with lower VAT 5 yr later (17). These results provide evidence that reallocating sedentary time with higher-intensity activity is important for adolescent development.…”
mentioning
confidence: 99%
“…Focusing on children, evidence from a systematic review supports that both the time expended and the intensity of PA are associated with beneficial effects on health 7 . Following these lines, the interruption of sedentary associated-behavior in children is suggested as a promising strategy to reduce cardiometabolic abnormalities 8 , 9 . Therefore, moving away from sedentary behavior is key to improving the cardiometabolic health of the youth population, especially after the negative impact of the pandemic and home lockdown 10 .…”
Section: Introductionmentioning
confidence: 99%